2016
DOI: 10.1063/1.4960526
|View full text |Cite
|
Sign up to set email alerts
|

Highly anisotropic electronic transport properties of monolayer and bilayer phosphorene from first principles

Abstract: The intrinsic carrier transport dynamics in phosphorene is theoretically examined.Utilizing a density functional theory treatment, the low-field mobility and the saturation velocity are characterized for both electrons and holes in the monolayer and bilayer structures. The analysis clearly elucidates the crystal orientation dependence manifested through the anisotropic band structure and the carrier-phonon scattering rates. In the monolayer, the hole mobility in the armchair direction is estimated to be approx… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 29 publications
5
21
4
Order By: Relevance
“…In contrast to the measurements by Cao [274] and the ab initio calculations by Jin et al [282], the bilayer mobilities obtained by Gaddemane et al [283] were almost identical or even smaller than in the monolayer.…”
Section: Phosphorenecontrasting
confidence: 78%
See 2 more Smart Citations
“…In contrast to the measurements by Cao [274] and the ab initio calculations by Jin et al [282], the bilayer mobilities obtained by Gaddemane et al [283] were almost identical or even smaller than in the monolayer.…”
Section: Phosphorenecontrasting
confidence: 78%
“…Jin et al [282] later calculated the intrinsic electron and hole mobilities of both monolayer and bilayer phosphorene, using a full-band Monte Carlo method for the solution of the BTE [23]. Their study confirmed earlier findings that the anisotropic crystal structure of phosphorene imparts anisotropic transport properties via the anisotropic band structure and scattering rates.…”
Section: Phosphorenesupporting
confidence: 56%
See 1 more Smart Citation
“…In the general case, including semiconductors, the major challenge is that the integrodifferential BTE does not have a closedform solution. Most approaches use then some form of relaxation-time approximation 24,[39][40][41][42][43][44][45][46][47][48][49] to obtain a closedform result.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has been studied extensively 24,40,41,43,44,60,[63][64][65][66][67][68][69][70][71][72][73][74][75] , showing excellent agreement 44 with experiments 1 and a detailed understanding of the main processes limiting mobility 41 , including the effects of dimensionality and charging by field effect 29,75 . MoS 2 , another prototypical 2D material, has also been studied in several works 24,42,43,[52][53][54] , as well as phosphorene [45][46][47][48]76,77 , arsenene [78][79][80] , silicene 24 , and other TMDs 42 . On the other hand, the effects of periodic images and dimensionality are explicitly treated only in some of the first-principles efforts 24,52,53 .…”
Section: Introductionmentioning
confidence: 99%